Circulating tumor DNA in early-stage colon cancer: ready for prime time or needing refinement?. (December 2022) - Solar Vasconcelos, Joao Paulo; Boutin, Melina; Loree, Jonathan M.
Liquid biopsies are the detection of molecular information in fluids from patients with cancer. In colorectal cancer (CRC), the most promising liquid biopsy strategy is the use of circulating tumor DNA (ctDNA) from plasma. In early-stage CRC, the potential for ctDNA to impact care stems from the detection of minimal residual disease (MRD) to guide adjuvant therapy after curative intent treatment and in identifying recurrences during surveillance. As for any new diagnostic test, ctDNA assays must overcome pre-analytical and analytical challenges before clinical implementation. We will discuss important logistical and assay considerations that clinicians and patients should understand when assessing ctDNA assays. We will also delve into important concepts to aid in interpreting ctDNA results and potential incidental findings that may arise. Sequencing errors, germline variants, and clonal hematopoiesis of indeterminate potential (CHIP) must be addressed to properly interpret results. CHIP is also an important consideration that impacts patient prognosis through association with cardiovascular and hematologic diseases. With this background in place, we next review the best available evidence for the use of ctDNA in early-stage colon cancer. Observational cohorts have established MRD after surgery as a significant prognostic factor for recurrence in stage II and III colon cancer. It also has the ability to anticipate clinical recurrence before standard investigations when used in surveillance. The first and only interventional randomized trial to date evaluating ctDNA is DYNAMIC. The study demonstrated the noninferiority of a MRD detection-guided approach in selecting patients with stage II colon cancer for adjuvant treatment. Notwithstanding the important results, there are still important questions to be answered before ctDNA enters prime time in the clinic. However, future appears bright and ongoing trials will help clarify how to best use this technology in early-stage colon cancer.